2023
DOI: 10.1007/s11440-023-01900-w
|View full text |Cite
|
Sign up to set email alerts
|

Long-term sinking of nuclear waste canisters in salt formations by low-stress creep at high temperature

Abstract: Rock salt has a self-sealing capacity, low permeability, and high thermal conductivity, making it a potential host for heat-generating nuclear waste. The feasibility of nuclear waste disposal within salt formations has been investigated mostly for small-sized canisters. Geologic disposal of larger-sized canisters originally designed for spent fuel storage and transportation has lately been examined as a cost-effective alternative. This raises questions about their long-term vertical movement due to their weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Kröhn et al (2017) reported discrepancies between the results of a triaxial test and an earlier oedometer test, particularly at small porosities. Consequently, previous generic modeling of the long-term behavior of nuclear waste repositories in salt predicted a rapid full reconsolidation of the backfill in less than 20 years (Lerch et al, 2012;Blanco-Martín et al, 2015a;Tounsi et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Kröhn et al (2017) reported discrepancies between the results of a triaxial test and an earlier oedometer test, particularly at small porosities. Consequently, previous generic modeling of the long-term behavior of nuclear waste repositories in salt predicted a rapid full reconsolidation of the backfill in less than 20 years (Lerch et al, 2012;Blanco-Martín et al, 2015a;Tounsi et al, 2023).…”
Section: Introductionmentioning
confidence: 99%